Higher Education and Regional Economic Coordination: Measurement and Evaluation, Influencing Factors, and Development Decisions - Shuxi Yan; Lifeng Guo; Liwei Sun (Decision Making: Applications in Management and Engineering, 2025)
Higher education relies on the support of the regional economy, while the demand for human capital to drive regional economic growth largely originates from higher education. Thus, their coordinated advancement is essential in the contemporary knowledge-based economy. This study establishes an indicator system and evaluates the current state of higher education and regional economic development. Utilising statistical data from Shaanxi Province spanning 2008 to 2022, the entropy method is applied to determine indicator weights. Decision analysis on the coordination level and influencing factors of higher education and regional economic development is conducted through statistical methods, including multiple linear regression, the coupling coordination model, and the obstacle degree model. Findings indicate a gradual strengthening in the coupling coordination degree, progressing from an initial phase of moderate imbalance to primary coordination. However, the overall coordination level remains low, highlighting the need for further integration. The limited developmental progress of both sectors acts as an internal constraint on their coordination. The three primary indicators impeding higher education advancement are the per-student public financial budget allocation for regular universities, the proportion of senior academics within full-time faculty, and the enrolment ratio of postgraduate students in regular universities. Additionally, enrolment figures frequently emerge as limiting factors. Regarding regional economic constraints, factors such as social retail sales, GDP index, and the proportion of employees in the tertiary sector hinder progress. Meanwhile, urbanisation functions as a significant catalyst, primarily enhancing coordination through its positive effect on developmental levels. Based on these findings, the study puts forward policy recommendations to foster deeper integration and coordination between higher education and regional economic development.